Improvement of mechanical properties of hydroxyapatite composites reinforced with i-Al64Cu23Fe13 quasicrystal - Castaneda-Via, Jose (2021)
The author(s) disclosed receipt of the following financial support for the research, authorship, and/or publication of this article: J.C.-V. thanks to Circulo de Investigacion e Innovacion de Materiales Avanzados para la Industria y Biomedicina of FONDECYT (CONCYTEC) under grant No 011-2014-FONDECYT, and to the Brazilian Society of Physics (PLAF program) that financed part of this work. C. V.L., J.Q.-M. and V.P.R. are grateful to FONDECYT (CONCYTEC) for financial support through the Excellence Center Program.